An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Unlocking dual-site regulation in perovskite-modified separators for efficient polysulfide conversion in lithium-sulfur batteries - Mingxu Li; Byeong hun Oh; Heejin Kim; Dong-Ho Baek; Ying Liu; Dengzhou Liu; Zabrian Dirfan; SuHyeon Ahn; Rong Yang; Jou-Hyeon Ahn; Inseok Seo; Du-Hyun Lim; et al. (Chemical Engineering Journal, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Defect-anchored confinement of Pt–In clusters via atomic layer deposition in hierarchical ZSM-5 for durable propane dehydrogenation - Jie Xu; Yi Yu; Chun Du; Yanfei Liu; Yaohui Dun; SenSen Yu; Fudong Liu; Yunsheng Dai; Rong Chen; Bin Shan (Chemical Engineering Journal, 2026)

Polyhydroxybutyrate production-oriented wastewater valorization: Aniline as a selective stress enabling non-sterile operation - Chunyu Du; Ziqian Wang; Rong Li; Guanyu Zheng; Dahu Ding (Water Research, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Oxidation byproducts in advanced water treatment: Formation mechanisms, toxicity attribution, and risk-oriented assessment - Yiran Jia; Rong Xiao; Naiyuan Liu; Congcong Li; Zhangbin Pan; Leran Liu; Zhenqi Du; Ruibao Jia (Journal of Water Process Engineering, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

Immunomodulatory effects of sea buckthorn leaf green tea in cyclophosphamide-induced immunosuppressed mice - Xuhui Kan; Yingjia Yao; Zengshan Chen; Haihong Wang; Chao Che; Quanjin Rong; Fengfeng Du; Jixiang Liu; Xixi Li; Xiaojing Liu; Dongrui Yao (Food Research International, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Rigid polyaniline interlayer pillar enables high-capacity and stable FeVO4 cathode for aqueous zinc-ion batteries - Zefeng Xu; Wenyan Du; Rong Gu; Yaokang Lv; Ziyang Song; Lihua Gan; Mingxian Liu (Chemical Engineering Journal, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Regulatory role of the keystone taxa Dokdonella in bacterial network stability under grazing disturbance in alpine meadows - Hainian Lu; Jiaoyang Du; Yongli Xie; Yu Zou; Xiujin Zhang; Dingan Gao; Xiaohui Wu; Chaokun Wang; Rong Wang (Rhizosphere, 2026)

Stabilizing flow and enhancing recovery: the dual role of scale inhibitors in neutral uranium leaching - Cong Huang; Jiacheng Guo; Hao Jin; Yiduo Du; Rong Hua; Xuebin Su (Minerals Engineering, 2026)

Determining an optimal sample size range for UAV-assisted satellite soil moisture content retrieval using a farthest point sampling method - Furong Yang; Ning Geng; Yifei Yao; Rong Liu; Zugui Huang; Shikun Sun; Yadan Du (Journal of Hydrology, 2026)

Moderate grazing disturbance enhances network stability and ecological functions of rhizobacteria in Alpine meadows: Identification and validation of Core genera - Hainian Lu; Jiaoyang Du; Yongli Xie; Dingan Gao; Xiaohui Wu; Feifei Chang; Liyang Duan; Xuerui Wang; Rong Wang (CATENA, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Associations of High Serum Ferritin Concentrations with Learning Disability and Attention Deficit/Hyperactivity Disorder among Children and Adolescents - Xueya Xiao; Buyun Liu; Yuhong Xiong; Zelong Wangchen; Wei Bao; Shuang Rong; Meiyuan Chen; Yang Du; Linda G. Snetselaar; Guifeng Xu (Journal of the Academy of Nutrition and Dietetics, 2026)

From byproduct to bioresource: Antioxidant potential, flavor profile, and microbiological quality of recovered water from freeze-dried and rotary evaporation dried Muscat grapes - Mengru Li; Yilei Huo; Pengkai Tang; Xiaoying Zhang; Haiyu Du; Wuernisha Kadeer; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2026)

Identification of CAMTA transcription factors and functional analysis of OsCAMTA4 in rice blast and salt stress - Zixiang Li; Zhensheng Qiao; Zhichao Wang; Rong Huang; Junxing Tan; Quchen Zhou; Xiangyu Huang; Feng Sheng; Xuezhu Du (Planta, 2026)

Shifts in microbial nutrient limitation drive microbial necromass carbon accumulation in mixed temperate plantations - Guohua Rong; Fan Du; Ying Zhang; Yaqi Dong; Hongyu Wu (Plant and Soil, 2026)

Manure compost and gypsum amendments revitalize soil quality via aggregation and pore structure in the Yellow River Delta - Xiaoyang Duan; Xiaoying Jin; Qi Miao; Zhanlonggang Yu; Hui Rong; Xiao Wang; Zhenling Cui; Hu Zhou; Zhangliu Du (Journal of Soils and Sediments, 2026)

Biocrust-forming mosses mediate bacterial community assembly in response to aridity across northern China - Fang Du; Xiaoying Rong; Xiaobing Zhou; Shen Yu; Zachary T. Aanderud; Yuanming Zhang (Applied Soil Ecology, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Overexpression of the MsCaM1 gene from alfalfa promoted growth and salinity tolerance in transgenic Arabidopsis - Rugang Yu; Xin Chen; Xinli Pan; Mengru Rong; Lin Yang; Guoliang Wang; Xueling Du (Journal of Plant Biochemistry and Biotechnology, 2026)

Antioxidant peptides from porcine blood meal: Mechanisms of interaction with hemin via spectroscopy and molecular docking - Rong Jia; Juanjuan Du; Jinxuan Cao; Jinpeng Wang; Yuemei Zhang; Wendi Teng; Ying Wang (Food Chemistry, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Non-Coding RNA Regulates Pyroptosis in Chronic Obstructive Pulmonary Disease - Xu Du; Yuan Geng; Wen-lan Fang; Yu-rong Chai (Phenomics, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sub/supercritical water liquefaction of discarded medical gloves: Aromatization and preparation of p-cymene - Fu-Rong Xiu; Jiao Du; Yan Zhang; Yingying Qi (Journal of Environmental Chemical Engineering, 2026)

Lightweight, flexible, multifunctional aluminum silicate fiber/polysiloxane aerogel composite with excellent thermal insulation under extreme environments for building applications - Xinwei Zhou; Rongying Yin; Yidan Jin; Yebo Du; Qin Rong; Haiming Cheng (Energy and Buildings, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

An arabinogalactan from Bupleurum chinense DC. attenuates LPS-induced inflammation in RAW264.7 macrophages - Bowen Zheng; Chenxu Jiang; Zheng Wang; Qiuhong Zhang; Hang Du; Nana Huang; Jin Wang; Jinhua Du; Daizhou Zhang; Rong Sun; Daijie Wang (Carbohydrate Polymers, 2026)

Design, synthesis, biological evaluation, and computational studies of chalcone scaffolds as cholinesterase inhibitors - Xue-Wei Zhou; Yi-Xuan Wang; Wen-Rong Du; Chao-Yue Zhang; Shi-Hao Qin; Zheng-Yue Ma (Medicinal Chemistry Research, 2026)

Isolation, Genome Sequencing and Proteomic Analysis of a LiCl-Tolerant Bacillus rugosus E-4 Strain from East Taijinar Salt Lake on the Qinghai-Tibet Plateau - Rong Xu; Sha Du; Zihua Liu; Miaomiao Hu; Jianlan Wu; Hongxia Zhu (Current Microbiology, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Synergistic and green decontamination of anion exchange resins: A surfactant and citric acid approach - Yukai Peng; YiChen Wu; Yiduo Du; Ye Tian; Xuebin Su; Rong Hua (Journal of Environmental Chemical Engineering, 2026)

Synthesis of novel aminomethyl phosphinic acid extractants and their use in the extraction and separation of zirconium and hafnium - Meiying Xie; Fan Yang; Rong Liu; Luyao Yang; Jinming Du; Xinyuan Lan; Minzhong Huang (Hydrometallurgy, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Using integrated multi-omics and molecular docking to decode stone epiphytic culture as a strategy for enhancing flavonoids and bioactivity in Dendrobium officinale leaves for functional tea development - Jing Li; Rong Zhou; Yingyue Hou; Yichang Chen; Shaohao Xie; Jinyu Wu; Jiang Chen; Hongbin Hou; Guangying Du (Food Bioscience, 2026)

Soil amendments improved physiological characteristics, grain yield, and water use efficiency of common buckwheat under multi-year continuous cropping - Qi Wang; Xiaoyi Han; Qixuan Wang; Minlong Du; Xinyue Lei; Jiahao Ge; Rong Zhong; Chenxi Wan; Xiaoli Gao; Pu Yang; Jinfeng Gao (European Journal of Agronomy, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Study on diagnosis of subclinical mastitis and identification of pathogens using electronic nose detection of cow’s milk - Fang Wang; Yujun Zhu; Enqiu Zhang; Rong Zhang; Hongwei Duan; Shuai Yang; Xianghong Du; Xingxu Zhao; Xiaofei Ma; Lihong Zhang; Junjie Hu (Computers and Electronics in Agriculture, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Morphological characteristics, molecular identification, and phylogenetic analysis of the four Leonurus species used for the treatment of gynecological diseases - Qing Du; Ziyi Rong; Yanjuan Guan; Chang Zhang; Liqiang Wang; Xiangyang Zhou; Chuanbei Jiang; Haidong Gao; Bin Wang; Haimei Chen; Chang Liu (Plant Gene, 2026)

Significant suppression of sulfur–containing organic aerosols by emission controls during the Hangzhou Asian Games - Jintian Zhang; Lei Liu; Jianxiong Rong; Lin Du; Zechen Yu; Shanshan Tang (Journal of Environmental Sciences, 2026)

Differential spatiotemporal distribution and assembly mechanisms of microeukaryotic generalists vs. specialists in the Bailong River Basin - Lingyun Chen; Rong Tang; Haifeng Du; Jianchuan Li; Alan Warren; Chengzhi Mao (Journal of Environmental Sciences, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Characterizing extreme climate events at different time scales and their contributions to agricultural drought and flooding areas - Rong Tang; Ying Xia; Junda Du; Long Qian; Hui Wang; Yangzan Ou (Natural Hazards, 2026)

Retrospective ENSO predictions using an intermediate ocean-atmosphere coupled model by integrating deep-learning sea surface wind stress - Shuangying Du; Rong-Hua Zhang; Chuan Gao (Journal of Oceanology and Limnology, 2026)

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Integrated sensing and communication for lettuce water-status monitoring - Ning Yang; Rong Du; Ni Yu; Wanting He; Zhenzhong Wang; Xiao Du; Si Chen (Computers and Electronics in Agriculture, 2026)

Effect of freeze–thaw treatment on physicochemical and antioxidant properties of Chinese hawthorn fruit and its juice - Rong Li; Chang Ma; Falong Du; Jiawei Cui; Yunfeng Hu; Junran Chen (Food Chemistry, 2026)

Bionic cellulose fiber-based columnar solar evaporator with interfacial regulation for superfast water purification - Ying Qian; Zhexuan Lan; Shunfang Wen; Rong Liu; Haifeng Zhang; Ruiqing Li; Du Nie; Seeram Ramakrishna; Wei Zhang; Jiamu Dai (Desalination, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Deep Learning-Based Object Detection of Electromagnetic Interference Echoes from Weather Radar Data - Man Yao; Muyun Du; Rong Yu; Xianling Jiang; Hedi Ma; Guoying Tang; Peiting Liu (Journal of Meteorological Research, 2026)

APOM Modulates the Glycolysis Process in Liver Cancer Cells by Controlling the Expression and Activity of HK2 via the Notch Pathway - Shuangqiu Du; Jingtong Wang; Miaomiao Liu; Rong Liu; Hui Wang; Yao Zhang; Fengcang Zhou; Wenjun Pei (Biochemical Genetics, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Predicting the occurrence of the emerging disinfection byproducts halocyclopentadienes and analyzing their driving factors in nationwide tap water using machine learning - Yongchang Xie; Quanzhen Liu; Tianhao Liu; Lihua Lin; Rong Li; Chuan Du; Wenru Bian; Donghong Wang (Water Research, 2026)

Preharvest melatonin application enhances soft rot resistance in kiwifruit through the jasmonic acid signaling pathway - Junsen Peng; Shufeng Du; Rong Fan; Youhua Long; Guofang Xie; Xiaochun Ding; Xiaoqing Dong (Postharvest Biology and Technology, 2026)

The candidate effector Bd_A04480 contributes to Botryosphaeria dothidea-induced postharvest soft rot in kiwifruit by increasing virulence and suppressing plant immunity - Hong Tan; Jinhuang Song; Juanrong Qin; Shufeng Du; Rui Yang; Xiaoqing Dong; Zhibo Zhao; Youhua Long; Rong Fan (Postharvest Biology and Technology, 2026)

pH-modulated assembly of meat protein by-products into Pickering stabilizers for high internal phase emulsions in clean-label condiment sauces - Nan Sun; Ruren Li; Mingying Du; Liangyan Rong; Guoliang Li (Food Chemistry, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Oyster-mussel differences in cadmium accumulation linked to molecular weight distribution of Cd-binding proteins - Guangbin Zhong; Xue Cao; Sen Du; Canchuan Zhang; Li Zhang; Niklas Helle; Minwei Xie; Rong Chen; Qiao-Guo Tan (Journal of Hazardous Materials, 2025)

Carbon emissions from desert soil regulated by non-rainfall water inputs and their potential mechanisms - Xing Guo; Fan Du; Jungang Yang; Shihang Zhang; Kai Shi; Yongxing Lu; Xiaoying Rong; Jun Zhang; Rongliang Jia; Lu Gong; Yuanming Zhang; Xiaobing Zhou (CATENA, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Confined Ostwald ripening approach towards highly durable and flexible 3D PTFE aerogels boosting Pickering emulsion separation in bi-phase photocatalysis - Yuxin Zhang; Jiawei Huangfu; Bin Rong; Xiongfei Du; Yang Hu; Xu Zeng; Kaikai Chen; Changkun Ding; Wenping Hu; Kuo Yuan; Qinglin Huang (Chemical Engineering Journal, 2025)

Treatment of waste PVC by subcritical nickel-containing electroplating wastewater: Crucial redox effect on PVC dechlorination and nickel removal - Fu-Rong Xiu; Yan Zhang; Jiao Du; Yingying Qi (Journal of Environmental Chemical Engineering, 2025)

Interfacial regulation of natural magnetite for oil-water separation in oily petrochemical wastewaters - Rong Wang; Jiarui Du; Junyi Li; Chenyang Zhang; Wei Sun (Journal of Environmental Chemical Engineering, 2025)

Morchella-inspired solar evaporator for anti-salt accumulation and highly efficient solar-driven interfacial evaporation - Rong Zhang; Renzhi Li; Zhiqiang Song; Pengjin Ye; Bo Du; Yongsheng Zhang; Bo Xiang (Journal of Environmental Chemical Engineering, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

Design, synthesis, biological evaluation, and in silico studies of cholinesterase inhibitors based on the 2-aminothiazole scaffold - Wen-Rong Du; Xue-Wei Zhou; Yi-Xuan Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

Induction of feline fetal fibroblasts into pluripotent stem cells using cat-derived reprogramming factors - Jian Qin; Nannan Sun; Yitong Wang; Jie An; Dipeng Zhao; Junling Li; Hao Zhang; Rong Du (Theriogenology, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Targeting mitochondrial dysfunction: an innovative strategy for treating renal fibrosis - Yi-Jin Wu; Yan-Rong Yang; Ya-Ling Yan; Han-Yinan Yang; Jun-Rong Du (Molecular and Cellular Biochemistry, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Pt decorated (CoMnFeCrNi)3O4 high-entropy oxide for low-temperature combustion of C3H8 - Lihong Xie; Yaohun Dun; Qiji Wang; Jie Xu; Song Li; Rong Chen; Chun Du; Bin Shan (Fuel, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Dl-3-n-Butylphthalide Promotes Neurogenesis in Ischemic Stroke Mice Through Wnt/β-Catenin Signaling Activation and Neurotrophic Factor Production - Lan Zhang; Cong Zhang; Rong Chen; Jian Zhang; Ying Liu; Yuanyuan Du; Xuan Gao; Wenyan Shang; Renhao Xu; Xiangjian Zhang (Molecular Neurobiology, 2025)

Parerythrobacter aurantius sp. nov., a Member of the Family Erythrobacteraceae Isolated from a Coastal Breakwater Stone - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Current Microbiology, 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Technological advances and sustainable strategies for electrolytic manganese wastewater treatment: A critical review - Chenyang Zhang; Ronghao Du; Rong Wang; Wei Sun; Yueping Luo; Zhiyuan Yu (Process Safety and Environmental Protection, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Analysis of anomalous cloud-to-ground lightning in a Wuhan tornadic supercell on 14 May 2021 - Rong Yu; Muyun Du; Dong Zheng; Jue Wang (Atmospheric Research, 2025)

Polyhydroxyalkanoates (PHA) production in a circular CO2 economy: it's role in mitigating global CO2 emissions - Zhiyuan Zong; Chitong Rao; Changjiang Du; Rong Lu; D.Chester Upham (Resources, Conservation and Recycling, 2025)

Megastigmane glycosides from Heterosmilax yunnanensis and their neuroprotective activity - Rong-Rong Du; Wen-Jie Qin; Xiu-Mei Duan; Xu Zhang; Ya-Nan Yang; Jian-Shuang Jiang; Xiang Yuan; Pei-Cheng Zhang (Phytochemistry, 2025)

Provenance and environmental changes recorded in Holocene sediments from the Southern Yellow Sea, China - Shuhuan Du; Rong Xiang; Xiang Su; Jianguo Liu; Shengfa Liu; Zirui Pan; Chuanxiu Luo; Fuchang Zhong; Li Fang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Myofibrillar protein aggregate evolution regulates interfacial adsorption behavior to maintain long-term stability of high internal phase Pickering emulsions - Jiaqi Zhao; Ruren Li; Futong Song; Mingying Du; Zhifu Liu; Liangyan Rong (Food Hydrocolloids, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Feasibility study of kinect home-based aerobic exercise assessment for pre-frail community-dwelling older adults - Wan-Yun Huang; Yi-Chun Du; Rong-Ju Cherng (Journal of Medical and Biological Engineering, 2025)

A chondroinductive peptide sustained-release platform design for cartilage regeneration after microfracture based on novel biomimetic recombinant protein film - Yukun Du; Yinhuan Xia; Shuang Wang; Jianyi Li; Guodong Zhang; Shuqing Chen; Xiaofan Du; Chongmin Ren; Rong-Chang Zeng; Yongming Xi; Weizhi Liu (Chemical Engineering Journal, 2025)

From field to food: Impact of nitrogen and phosphorus fertilizers on mung bean starch synthesis, structure, and functional properties - Jiahao Ge; Jie Li; Minlong Du; Xinyue Lei; Qi Wang; Rong Zhong; Qixuan Wang; Feng Gao; Xiaoli Gao; Baili Feng; Jinfeng Gao (Carbohydrate Polymers, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

[1H-13C]-NMR-Based Metabolic Kinetics Reveals Brain Neurochemical Alterations in Mice After Retinal Ischemia–Reperfusion Injury - Guojing Lu; Rong Huang; Siyu Zeng; Yiqiao Xing; Hang Xie; Lei Du (Molecular Neurobiology, 2025)

Regulating bacterial biofilms in food and biomedicine: unraveling mechanisms and Innovating strategies - Jun-Hu Cheng; Rong Du; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

A high-efficiency lettuce quality detection system based on FPGA - Zhenzhong Wang; Tongge Li; Rong Du; Ning Yang; Jianfeng Ping (Computers and Electronics in Agriculture, 2025)

An RCUNet-based sea surface wind stress model with multi-day time sequence information incorporated and its applications to ENSO modeling - Shuangying Du; Rong-Hua Zhang (Ocean Modelling, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Micromotors assisted in vivo dopamine polymerization for anti-tumor therapy - Dailing Du; Ye Feng; Miaomiao Ding; Jinghui Rong; Bin Chen; Chao Gao; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2025)

Antiviral potential of essential oils and their plant sources, delivery methods, and drug development strategies with special focus on their mechanisms: a comprehensive review - Anjie Feng; Tiantian Si; Baoxiang Du; Qihui Sun; Yong Yang; Rong Rong (Phytochemistry Reviews, 2025)

Design, synthesis, biological evaluation, and in silico studies of imidazo[2,1-b][1,3,4]thiadiazole derivatives as cholinesterase inhibitors - Wen-Rong Du; Yi-Xuan Wang; Xue-Wei Zhou; Yong Lan; Ben-Ben Wei; Xin-Yuan Guo; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

A comparative study of four color measurement methods for soil color identification and related properties prediction - Yuanyuan Du; Fengjin Kang; Zhangke Huang; Luyi Wang; Ya Zhang; Decheng Li; Guanghui Zheng; Rong Zeng (Computers and Electronics in Agriculture, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Reticulophagy promotes EMT-induced fibrosis in offspring’s lung tissue after maternal exposure to carbon black nanoparticles during gestation by a m5C-dependent manner - Zhe Du; Qingping Liu; Mengruo Wang; Yifu Gao; Qi Li; Yizhe Yang; Tianyu Lu; Lei Bao; Yaxian Pang; Haijun Wang; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2025)

Inhibition regulatory mechanism in Staphylococcus aureus under cold plasma oxidative stress - Rong Du; Xiao Yang; Jun-Hu Cheng (Food Bioscience, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Radiocarbon constraints on North Indian deep ocean ventilation and deglacial carbon dioxide release - Sui Wan; Yan Du; Lanlan Zhang; Liang Yi; Haowen Dang; Xiang Su; Jianguo Liu; Yiping Yang; Haoyin Wang; Rong Xiang (Quaternary Science Reviews, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

Antibacterial chitosan/organic rectorite nanocomposite-conjugated gelatin/β-cyclodextrin hydrogels with improved hemostasis performance for wound repair - Rong Huang; Yongqian Bian; Wenxuan Wang; Lirong Xu; Hao Zhang; Haowei Zhou; Jincheng Du; Jiaqi Li; Yuheng Zhang; Xueyong Li; Jing Li (Carbohydrate Polymers, 2025)

Study on the mechanism of brain injury caused by acute diquat poisoning based on metabolomics - Chaocheng Wang; Hui Hu; Junzhao Liu; Xia Rong; Jing Zhang; Yu Du (Toxicology and Applied Pharmacology, 2025)

Heavy metal(loid)s accumulation and human health risk assessment in wheat after long-term application of various urban and rural organic fertilizers - Ling Zhang; Wentao Xue; Hao Sun; Qinping Sun; Yuncai Hu; Rong Wu; Ying Du; Shanjiang Liu; Guoyuan Zou (Science of The Total Environment, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Abundance and community structure of comammox bacteria in the rhizosphere of aquatic plants in an urban eutrophic lake - Mingzhi Zhou; Rong Du; Ziyan Lei; Shuang Liu; Jianwei Zhao (Ecohydrology & Hydrobiology, 2025)

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

High-efficiency co-liquefaction of brominated epoxy resin and low rank coal in supercritical water: Waste recycling and products upgrading - Fu-Rong Xiu; Jiao Du; Yuze Chen; Xinyue Lei; Yingying Qi (Process Safety and Environmental Protection, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Holistic parameter sensitivity: A new perspective to address the risk brought by multi-source deep uncertainty on watershed management - Yi Rong; Siyu Zeng; Chengxin Qin; Yan Chen; Qiang Wang; Pengfei Du (Journal of Environmental Management, 2024)

Optimizing interactions for efficient hydrogen evolution reaction by incorporating rhenium nanoparticles on defect-rich carbon - Yi-Sha Ba; Wen Lei; Xin Du; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

In situ testing of micro-ecological elements in offshore engineering - Dingtian Yang; Ranran Du; Linhong Zhao; Rong Zhong; Xiangqian Quan (Ocean Engineering, 2024)

Spatial and temporal dynamics of microbes and genes in drinking water reservoirs: Distribution and potential for taste and odor generation - Xuanzi Zhangsun; Honghong Guo; Quanjie Du; Na Li; Shuhong Xue; Rong Li; Wenrui Ma; Xiang Liu; Haihan Zhang; Tinglin Huang (Journal of Hazardous Materials, 2024)

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Obtaining phenolic-rich extracts from tree nut shells biomass by room temperature green extraction: Molecular insights and attribution analysis - Ruoyu Du; Zhaobao Xiang; Xue Yang; Xinling Zhao; Qingya Cao; Rong Peng; Guizhi Zhang; Zhongyi Yin (Sustainable Chemistry and Pharmacy, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

Identification of peptides from Corneum Galli Gigeri Endothelium and inhibiting H2O2-induced gastric mucosa associated with the Rho signaling pathway - Rong xiang Guo; Huiying Zhang; Yao Chen; Pan Li; Bing Du (Food Bioscience, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

Constructing ultralow-loading Cu single atoms/Fe2O3 particles on Nb2C MXenes for efficient utilization of atomic H to boost electrochemical debromination - Fangxian Wang; Junwei Yang; Shihao Li; Junwen Liang; Yuwei Wang; Rong Du; Bo Zhou; Qiong Liu; Changping Li (Chemical Engineering Journal, 2024)

Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Wen-Rong Du; Ben-Ben Wei; Xin-Yuan Guo; Yong Lan; Pan-Pan Shang; Yi-Xuan Wang; Xue-Wei Zhou; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

Management of zooplanktonic predations for efficient and sustainable production of Arthrospira - Xiaobin Wen; Rongxiang Lü; Junying Zhu; Du Cao; Junfeng Rong; Weichun Du; Yeguang Li (Algal Research, 2024)

Tracking the impact of perfluoroalkyl acid emissions on antibiotic resistance gene profiles in receiving water by metagenomic analysis - Nannan Lu; Zhenqi Du; Fumin Chu; Rong Xiao; Zhengdi Wu; Mingquan Wang; Ruibao Jia; Wenhai Chu (Water Research, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Biofilm growth characteristic and footprint identification in gravity-driven ceramic membrane bioreactor with electro-coagulation under extreme conditions for roofing rainwater purification - Wei Song; Rong Ma; Zhenhao Liang; Jiawan Li; Jiahao Dong; Xing Du; Zhihong Wang; Xianhui Li (Journal of Environmental Management, 2024)

Advances in treatment technologies for silver-containing wastewater - Heng Yu; Hongliang Zhang; Chenyang Zhang; Rong Wang; Siyuan Liu; Ronghao Du; Wei Sun (Chemical Engineering Journal, 2024)

Albumin tailoring molecular rotation and electrophilicity of a GSH-depleting radiosensitizer for potentiating ferroptosis-mediated radioimmunotherapy - Mingquan Gao; Xie Huang; Zifei Wu; Weidong Xiao; Zaizhi Du; Banghui Mo; Chuan Wu; Haiyan Xing; Weidong Wang; Rong Li; Shenglin Luo (Chemical Engineering Journal, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Constructing Cu9S5@CuSe heterostructures under microwave irradiation for rechargeable magnesium batteries - Mingwei Jin; Zhaoyu Xue; Heng Cao; Qianwei Zhang; Rong Jiang; Changliang Du; Lifen Yang; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Investigation of New Integrated Drought Monitoring Model Taking into Account the Effects of Climate Anomalies - Lei Zhou; Wenliang Wang; Congcong He; Siyu Wang; Yalan Li; Rong Tian; Cheng Du (Journal of the Indian Society of Remote Sensing, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

U-Net Models for Representing Wind Stress Anomalies over the Tropical Pacific and Their Integrations with an Intermediate Coupled Model for ENSO Studies - Shuangying Du; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2024)

Sulfur migration mechanism of pig manure in supercritical water: A combined experimental and DFT study - Shuyuan Zhang; Mingming Du; Hui Ge; Siqi Rong; Yunan Chen; Liejin Guo (Journal of Hazardous Materials, 2024)

Effects of carnosine combined with Lactobacillus on the antioxidant capacity of liver and kidney in normal or stressed mice - Jian Qin; Yue Ma; Conghui Wang; Huiying Li; Zhiqiang Zou; Yunqing Zhang; Jing Ma; Rong Du (Food Bioscience, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

3-D imaging of whole-space environments with electromagnetic induction sensors based on linear approximation - Jintai Li; Jianxin Liu; Wenxiang Liu; Rongwen Guo; Kun Du; Rong Liu (Tunnelling and Underground Space Technology, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Microwave-induced defect-rich vanadium sulfide cathodes for highly reversible electrochemical magnesium storage - Rong Jiang; Bolin Liu; Changliang Du; Mingwei Jin; Xin Liu; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Cytogenetic analysis reveals a mechanism of compatibility in distant hybridization between tree peony and herbaceous peony - Yuan Zhong; Ming-jie Du; Run-ze Ji; Qi Rong; Zi-heng Guan; Fang-yun Cheng (Euphytica, 2024)

Hub gene ELK3-mediated reprogramming lipid metabolism regulates phenotypic switching of pulmonary artery smooth muscle cells to develop pulmonary arterial hypertension induced by PM2.5 - Qingping Liu; Yizhe Yang; Mengqi Wu; Mengruo Wang; Peihao Yang; Jie Zheng; Zhe Du; Yaxian Pang; Lei Bao; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

Taking full advantage of ‘low-quality’ datasets in watershed modeling and management: From a perspective of parameter calibration - Yi Rong; Chengxin Qin; Haw Yen; Fu Sun; Pengfei Du; Siyu Zeng (Journal of Environmental Management, 2024)

Provenance of the Lower Jurassic pyroclastic sediments in the Zigui Basin: Implication for crustal thickening in the eastern Qinling orogenic belt - Rong Chai; Jianghai Yang; Yuansheng Du; Chengshan Wang (Science China Earth Sciences, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Alkaline chlorination of drinking water: A trade-off between genotoxicity control and trihalomethane formation - Chao Fang; Wenyuan Yang; Nannan Lu; Rong Xiao; Zhenqi Du; Qi Wang; Wenhai Chu (Water Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

G-quadruplex based biosensors for the detection of food contaminants - Rong Du; Xiebingqing Yang; Ping Jin; Yahui Guo; Yuliang Cheng; Hang Yu; Yunfei Xie; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2023)

The impact of industrial aggregation on carbon emission intensity: evidence from the grain and oil processing sector - Youshuai Feng; Shuchao Miao; Rong Du (Environment, Development and Sustainability, 2023)

Disinfection by-product precursors introduced by sandstorm events: Composition, formation characteristics and potential risks - Zhenqi Du; Shunke Ding; Rong Xiao; Chao Fang; Ruibao Jia; Wenhai Chu (Water Research, 2023)

Soil core microbiota drive community resistance to mercury stress and maintain functional stability - Shuai Du; Xin-Qi Li; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Science of The Total Environment, 2023)

Uncovering the relational upgrading of the iron product network in China - Hui Chen; Peilin Du; Yu Ni; Mei Rong (Resources, Conservation and Recycling, 2023)

Prediction of the rate of penetration in offshore large-scale cluster extended reach wells drilling based on machine learning and big-data techniques - Xuyue Chen; Chengkai Weng; Xu Du; Jin Yang; Deli Gao; Rong Wang (Ocean Engineering, 2023)

Ultrasensitive detection and efficient removal of mercury ions based on covalent organic framework spheres with double active sites - Ke Xiao; Rong Zhu; Xiaohua Zhang; Cuicui Du; Jinhua Chen (Analytica Chimica Acta, 2023)

Site-specific Atg13 methylation-mediated autophagy regulates epithelial inflammation in PM2.5-induced pulmonary fibrosis - Jie Ning; Zijie Pei; Mengruo Wang; Huaifang Hu; Meiyu Chen; Qingping Liu; Mengqi Wu; Peihao Yang; Zihan Geng; Jie Zheng; Zhe Du; Wentao Hu; et al. (Journal of Hazardous Materials, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

Potential candidate genes and pathways related to cytoplasmic male sterility in Dianthus spiculifolius as revealed by transcriptome analysis - Yingzhu Liu; Han Sun; Rong Ye; Jinxue Du; Haizhen Zhang; Aimin Zhou; Kun Qiao; Jingang Wang (Plant Cell Reports, 2023)

CLASRP oncogene as a novel target for colorectal cancer - Quan Gu; Jianzhong Wu; Heng Xu; Haixia Cao; Junying Zhang; Changwen Jing; Zhuo Wang; Mengjie Du; Rong Ma; Jifeng Feng (Functional & Integrative Genomics, 2023)
Clk4-associated serine/arginine-rich protein ( CLASRP ), an alternative splicing regulator, may be involved in the development and progression of cancer by regulating the activity of the CDC-like kinase (Clk) family. This study explored the biological function of CLASRP in colorectal cancer (CRC). The expression of CLASRP , which is associated with clinicopathological features, was analysed in CRC tissues and paired noncancer tissues by RT–PCR. The roles of CLASRP were investigated in CRC cells transfected with plasmids or shRNA through proliferation, migration and invasion assays in vitro and a xenograft model in vivo . Apoptosis was analysed using CLASRP -overexpressing CRC cells by western blotting. Clk inhibitors were used to perform functional research on CLASRP in CLASRP -overexpressing CRC cells. CLASRP was significantly upregulated in CRC cell lines, while high CLASRP expression was correlated with metastasis in CRC patients. Functionally, overexpression of CLASRP significantly promoted the proliferation, migration and invasion of CRC cells in vitro and tumour growth in vivo. Mechanistically, the proliferation, migration and invasion of CLASRP -overexpressing CRC cells were inhibited by Clk inhibitors, accompanied by low expression of CLASRP at the gene and protein levels. Clk inhibitors induced apoptosis of CLASRP -overexpressing CRC cells, resulting in direct blockade of cell growth. The expression levels of cleaved caspase 3 and cleaved caspase 8 were increased in CLASRP -overexpressing CRC cells treated with Clk inhibitors. CLASRP might serve as a promotional oncogene in CRC cells and be suppressed by Clk inhibitors through activation of caspase pathways.

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Retzius periodicity in the Late Miocene hominoid Lufengpithecus lufengensis from Southwest China: Implications for dental development and life history - Rong Hu; Baopu Du; Lingxia Zhao (Journal of Human Evolution, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Evolution of the structure of meat protein particles at the oil–water interface facilitates the ultra-long storage stability of high internal pickering emulsion - Shuyu Tan; Mingying Du; Gaibo Yuan; Liangyan Rong; Ruren Li; Guoliang Li (Food Hydrocolloids, 2023)

Transformation of cognition from mechanical to biological aqueous outflow pump may be a breakthrough in solving the problem of intraocular pressure regulation in glaucoma - Shen Wu; Chen Xin; Wei Zhu; Yue Wan; Qing Sang; Rong Du; Jian Wu; Jin Wang; Ningli Wang (Science China Life Sciences, 2023)

Divergence in the distribution of di(2-ethylhexyl) phthalate (DEHP) in two soils - Qiutang Wang; Yanwen Xu; Wenchao Du; Ying Yin; Xuan Wu; Feifei Sun; Rong Ji; Hongyan Guo (Environmental Science and Pollution Research, 2023)

Identification of key precursors contributing to the formation of CX3R-type disinfection by-products along the typical full-scale drinking water treatment processes - Xu Yang; Shunke Ding; Rong Xiao; Pin Wang; Zhenqi Du; Ruihua Zhang; Wenhai Chu (Journal of Environmental Sciences, 2023)

Experimental study on optimizing reaction path for promoting the gasification of coal in supercritical water - Jingli Sun; Mingming Du; Siqi Rong; Jialing Xu; Hui Jin; Liejin Guo (Fuel, 2023)

Manganese oxide nanocrystals embedded porous Graphene-like network for electrosynthesis of H2O2 and construction of Self-powered aptasensor - Chuanpan Guo; Yiming Ruan; Shuai Zhang; Lun Kan; Heng Bian; Feilong Rong; Linghao He; Dongsheng Li; Miao Du; Zhihong Zhang (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Genome resequencing reveals genetic loci and genes conferring resistance to SMV-SC8 in soybean - Jiahao Chu; Wenlong Li; Zhanwu Yang; Zhenqi Shao; Hua Zhang; Shaoda Rong; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

CircBCL11B acts as a ceRNA to facilitate 1,2-dichloroethane-induced astrocyte swelling via miR-29b-3p/AQP4 axis in SVG p12 cells - Yizhou Zhong; Bingli Zhang; Yuji Huang; Jiaxin Du; Boxuan Liang; Zhiming Li; Rongyi Ye; Bo Wang; Hongyi Xian; Xifei Yang; Weifeng Rong; Xiang Guo; et al. (Toxicology Letters, 2023)

Northward migration of the maximum Indian summer monsoon precipitation during the early–mid-Holocene: Evidence from sporopollen in the Andaman Sea - Zijie Yang; Chuanxiu Luo; G.M. Ariful Islam; Xuhui Dong; Xiang Su; Rong Xiang; Shuhuan Du; Yiping Yang; Shengfa Liu (Marine Micropaleontology, 2023)

Effects of a calcium/vitamin D/Zinc combination on anti-osteoporosis in ovariectomized rats - Shanshan Wang; Zhen Luo; Hujie Luo; Zhiwei Li; Zhengqiang Yuan; Jian Tang; Li Lin; Zhiyun Du; Jin-Rong Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Impact of the Western Pacific Warm pool and Kuroshio dynamics in the Okinawa Trough during the Holocene - Sui Wan; Rong Xiang; Stephan Steinke; Yan Du; Yiping Yang; Shuhong Wang; Haoyin Wang (Global and Planetary Change, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Early warning and scenario simulation of ecological security based on DPSIRM model and Bayesian network: A case study of east Liaohe river in Jilin Province, China - Walian Du; Xiaoyu Liao; Zhijun Tong; Su Rina; Guangzhi Rong; Jiquan Zhang; Xingpeng Liu; Enliang Guo (Journal of Cleaner Production, 2023)

Insight into the purification of algael water by a novel flocculant with enhanced branched nanochitosan structure - Bin Du; Qian Tang; Wei Chen; Xiang Rong; Ke Zhang; Dandan Ma; Zhaolan Wei; Wei Chen (Journal of Environmental Management, 2023)

Controllable Pd@Cu2O Schottky junction interface with improved anti-poisoning effect for efficiently electroreduction of CO2 into syngas - Rong Cai; Xin Du; Guorui Liu; Xiuli Wang; Qiang Tang; Xinpin Pan; Feng Li; Jing Li (Fuel, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

The inhibition mechanism and death mode of Microcystis aeruginosa induced by the continuous pressure of artemisinin sustained-release microspheres (ASMs) - Cunhao Du; Lixiao Ni; Jakpa Wizi; Wenlu Sang; Shiyi Rong; Xianglan Li; Chu Xu; Yan Li; Xuqing Chen; Shiyin Li (Algal Research, 2023)

Does the differentiated blue product structure affect country's blue economy status? Evidence from complex network and spatial econometric analysis - Yu Ni; Peilin Du; Mei Rong (Environment, Development and Sustainability, 2023)

High-resolution palynology signals in surface sediments of coastal Hainan Island of China - Dileep B. Herath; Chuanxiu Luo; Chixin Chen; Shuhuan Du; Rong Xiang; Vidusanka Thilakanayaka; Gayan Bandara; Dhanushka Devendra; Zijie Yang; Thilina Munasinghe (Marine Micropaleontology, 2023)

Meal Skipping and Shorter Meal Intervals Are Associated with Increased Risk of All-Cause and Cardiovascular Disease Mortality among US Adults - Yangbo Sun; Shuang Rong; Buyun Liu; Yang Du; Yuxiao Wu; Liangkai Chen; Qian Xiao; Linda Snetselaar; Robert Wallace; Wei Bao (Journal of the Academy of Nutrition and Dietetics, 2023)

Adaptive evaluation of green manure rotation for a low fertility farmland system: Impacts on crop yield, soil nutrients, and soil microbial community - Rong Yang; Shujun Song; Shiyang Chen; Zeyu Du; Junqia Kong (CATENA, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

The distinct fruit size and physical defense promote divergent secondary seed dispersal strategies of three oak species - Xi Chen; Yanjun Luo; Rong Wang; Fang K. Du (Forest Ecology and Management, 2023)

A new method for wear estimation of TBM disc cutter based on energy analysis - Lei She; She-rong Zhang; Chao Wang; Yan-long Li; Min Du (Tunnelling and Underground Space Technology, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Enhanced preservation effects of clove (Syzygium aromaticum) essential oil on the processing of Chinese bacon (preserved meat products) by beta cyclodextrin metal organic frameworks (β-CD-MOFs) - Ying Wang; Yi-Tong Du; Wan-Yu Xue; Liang Wang; Rong Li; Zi-Tao Jiang; Shu-Hua Tang; Jin Tan (Meat Science, 2023)

Elevated CO2 aggravated polystyrene microplastics effects on the rice-soil system under field conditions - Meiling Xu; Qiao Xu; Guobing Wang; Wenchao Du; Jianguo Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Environmental Pollution, 2023)

Regulatory effects mediated by ulvan oligosaccharide and its zinc complex on lipid metabolism in high-fat diet-fed mice - Yongzhou Chi; Zhihua Wu; Chunying Du; Man Zhang; Xinyu Wang; Aowei Xie; Peng Wang; Rong Li (Carbohydrate Polymers, 2023)

Impact of repeated intravenous infusions of umbilical cord–derived versus bone marrow–derived mesenchymal stem cells on angiogenesis in a pregnant experimentally induced deep venous thrombosis rat model - Xi Cheng; Weina Wang; Rong Du; Mu Zhang; Yuanyuan Xie; Weiwei Sun; Jingjing Ji; Baolan Sun; Yuquan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Fbxw17 is dispensable for viability and fertility in mice - Zhen Chen; Dupeng Ma; Tingyu Jin; Ziqi Yu; Jiong Li; Qi Sun; Zejia Li; Ziye Du; Rong Liu; Yi Li; Mengcheng Luo (Molecular Biology Reports, 2022)

Dynamic Cause of the Sudden Death Event of Small Yellow Croaker (Larimichthys polyactis) in the East China Sea in Winter 2017 - Zilu Wei; Xiaohui Jiao; Jicai Zhang; Yunfei Du; Zengrui Rong; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ), a benthic fish species widely distributed in the Northwest Pacific Ocean, plays an important role in the fishery catch of coastal countries. A large amount of dead small yellow croaker floated on the sea surface near 30.2°N, 125.3°E in the East China Sea on 19 February 2017, and more than 9,000 kilograms were caught by fishermen, which had never been recorded before. This study aims to investigate the dynamic causes of this sudden death event based on available in-situ, satellite and modelling data. The event occurred near the overwintering ground of small yellow croaker, where a majority of these fish assembled in winter. There were persistent ocean fronts at target site with average intensity of 0.05°C/km at sea surface and bottom in February 2017, which was the strongest in the past 5 years from 2015 to 2019. The fronts provided nutrients and food to fish, and the intense gradients prevented fish from crossing, thus forming “water barriers” to restrict the horizontal movement of fish. Due to enhanced convection, the water was well-mixed, enabling the demersal croaker to float to sea surface. The sea temperature was particularly warm in winter 2017, but then experienced a significant drop by more than 4.5°C in 40 days according to satellite and modelling datasets due to the northerly wind and the southeastward movement of cold eddy. The drop of temperature led to ‘cold shock’ of fish, affecting their physiological regulation and survival. Under the combined influence of these factors, a large number of small yellow croaker died and aggregated near the target site. This paper has a great reference value for further study on the living habits of small yellow croaker and their responses to marine dynamic changes.

A low-cost in-situ CO2 sensor based on a membrane and NDIR for long-term measurement in seawater - Meng Li; Baolu Du; Jinjia Guo; Zhihao Zhang; Zeyu Lu; Rong’er Zheng (Journal of Oceanology and Limnology, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Regulation of β1-integrin in autophagy and apoptosis of gastric epithelial cells infected with Helicobacter pylori - Boqing Li; Qianyu Rong; Yunqiu Du; Ruiqing Zhang; Jing Li; Xiaohan Tong; Li Geng; Ying Zhang (World Journal of Microbiology and Biotechnology, 2022)

Croceicoccus gelatinilyticus sp. nov., isolated from a tidal flat sediment - Tao Pei; Yang Liu; Juan Du; Kunpeng Huang; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Examining the efficacy of revegetation practices in ecosystem restoration programs: insights from a hotspot of sandstorm in northern China - Ziqiang Du; Rong Rong; Zhitao Wu; Hong Zhang (Frontiers of Earth Science, 2021)

Inhella proteolytica sp. nov. and Inhella gelatinilytica sp. nov., two novel species of the genus Inhella isolated from aquaculture water - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2021)

Microvesicles derived from human umbilical cord mesenchyme promote M2 macrophage polarization and ameliorate renal fibrosis following partial nephrectomy via hepatocyte growth factor - Tao Du; Guanqun Ju; Jun Zhou; Liang Zhong; Lu Rong; Wenxia Chen; Xiaoli Zhang; Ruijin Zhou; Degang Ding; Tongyu Ji (Human Cell, 2021)

MiR-146a Negatively Regulates Aspergillus fumigatus-Induced TNF-α and IL-6 Secretion in THP-1 Macrophages - Jianbo Tong; Zhimin Duan; Rong Zeng; Leilei Du; Song Xu; Liwei Wang; Yuzhen Liu; Qing Chen; Xu Chen; Min Li (Mycopathologia, 2021)

Neuroprotective Effect of Phthalide Derivative CD21 against Ischemic Brain Injury:Involvement of MSR1 Mediated DAMP peroxiredoxin1 Clearance and TLR4 Signaling Inhibition - Xiao Zou; Xiao-Jia Yang; Yu-Miao Gan; Dong-Ling Liu; Chu Chen; Wei Duan; Jun-Rong Du (Journal of Neuroimmune Pharmacology, 2021)

Disrupted morphological grey matter networks in early-stage Parkinson’s disease - Xueling Suo; Du Lei; Nannan Li; Wenbin Li; Graham J. Kemp; John A. Sweeney; Rong Peng; Qiyong Gong (Brain Structure and Function, 2021)
While previous structural-covariance studies have an advanced understanding of brain alterations in Parkinson's disease (PD), brain–behavior relationships have not been examined at the individual level. This study investigated the topological organization of grey matter (GM) networks, their relation to disease severity, and their potential imaging diagnostic value in PD. Fifty-four early-stage PD patients and 54 healthy controls (HC) underwent structural T1-weighted magnetic resonance imaging. GM networks were constructed by estimating interregional similarity in the distributions of regional GM volume using the Kullback–Leibler divergence measure. Results were analyzed using graph theory and network-based statistics (NBS), and the relationship to disease severity was assessed. Exploratory support vector machine analyses were conducted to discriminate PD patients from HC and different motor subtypes. Compared with HC, GM networks in PD showed a higher clustering coefficient ( P = 0.014) and local efficiency ( P = 0.014). Locally, nodal centralities in PD were lower in postcentral gyrus and temporal-occipital regions, and higher in right superior frontal gyrus and left putamen. NBS analysis revealed decreased morphological connections in the sensorimotor and default mode networks and increased connections in the salience and frontoparietal networks in PD. Connection matrices and graph-based metrics allowed single-subject classification of PD and HC with significant accuracy of 73.1 and 72.7%, respectively, while graph-based metrics allowed single-subject classification of tremor-dominant and akinetic–rigid motor subtypes with significant accuracy of 67.0%. The topological organization of GM networks was disrupted in early-stage PD in a way that suggests greater segregation of information processing. There is potential for application to early imaging diagnosis.

Copper-promoted heterogeneous Fenton-like oxidation of Rhodamine B over Fe3O4 magnetic nanocatalysts at mild conditions - Wei Du; Ran Huang; Xuanlin Huang; Rong Chen; Fengxi Chen (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

The Dust Deposition Process and Biogeochemical Impacts in the Northern South China Sea - Shuhuan Du; G. M. Ariful Islam; Rong Xiang; Xiaoli Yang (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

Correction of seismic attribute-based small-structure prediction errors using GPR data—A case study of the Shuguang Coal Mine, Shanxi - Cui Fan; Zhao Zhi-Rong; Du Yun-Fei; Bai Yu; Xu Chang-Qing; Jia Xiao-Feng (Applied Geophysics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

ERas regulates cell proliferation and epithelial–mesenchymal transition by affecting Erk/Akt signaling pathway in pancreatic cancer - Yang Liu; Peng Qin; Rong Wu; Lianfang Du; Fan Li (Human Cell, 2020)
Pancreatic cancer is the fourth most common lethal malignancy with an overall 5-year survival rate of less than 5%. ERas, a novel Ras family member, was first identified in murine embryonic stem cells and is upregulated in various cancers. However, the expression and potential role of ERas in pancreatic cancer have not been investigated. In this study, we found that ERas mRNA and protein were upregulated in pancreatic cancer tissues and cells compared with controls. Knockdown of ERas in pancreatic cancer cells by siRNA significantly decreased cell proliferation, colony formation, migration, and invasion and promoted cell apoptosis in vitro. Epithelial–mesenchymal transition (EMT) is closely related to tumor progression. We observed a significant decrease in N-cadherin expression in pancreatic cancer cells in response to ERas gene silencing by immunofluorescence assay and western blot. Furthermore, tumor growth and EMT were inhibited in xenografts derived from pancreatic cancer cells with ERas downregulation. We further investigated the regulatory mechanisms of ERas in pancreatic cancer and found that ERas may activate the Erk/Akt signaling pathway. Moreover, Erk inhibitor decreased pancreatic cancer cells proliferation and colony formation activities. Our data suggest that targeting ERas and its relevant signaling pathways might represent a novel therapeutic approach for the treatment of pancreatic cancer.

Composition and functional diversity of fecal bacterial community of wild boar, commercial pig and domestic native pig as revealed by 16S rRNA gene sequencing - Jinqing Huang; Wenjuan Zhang; Rong Fan; Zhanggen Liu; Tao Huang; Junyi Li; Tonghao Du; Tao Xiong (Archives of Microbiology, 2020)

Triterpene-Enriched Olive Extract as an Immunopotentiator in Black Sea Bream (Acanthopagrus schlegelii) - Jiahuan Rong; Yu Han; Shanjie Zha; Yu Tang; Wei Shi; Xiaofan Guan; Xueying Du; Maolong He; Guangxu Liu (Journal of Ocean University of China, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Changes in air temperature over China in response to the recent global warming hiatus - Qinqin Du; Mingjun Zhang; Shengjie Wang; Cunwei Che; Rong Ma; Zhuanzhuan Ma (Journal of Geographical Sciences, 2019)

Description of Haemaphysalis (Alloceraea) Kolonini sp. nov., a new species in subgenus Alloceraea Schulze (Ixodidae: Haemaphysalis) in China - Chun-Hong Du; Yi Sun; Rong-Man Xu; ZongTi Shao (Acta Parasitologica, 2018)
Southeastern Asia has been postulated as probably the original sites of genus Haemaphysalis , where numerous structurally advanced haemaphysalids now occur. Because of its phylogenetic and biological interest, we report the discovery of a structurally primitive new species Haemaphysalis ( A .) kolonini belonging to subgenus Alloceraea from Baoshan and Weixi cities, Yunnan province, southwestern China. Both the morphological and phylogenic characteristics of the species support congruently to erect Hae . ( A .) kolonini as a new species. The male and female adults of Haemaphysalis ( A .) kolonini are respectively described and illustrated. Taxonomic discussion and keys to Alloceraea species in China are also provided to be able to distinguish species that are close morphologically.

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Carbonate formation mechanism in paleosol sediments of the Bohai Sea coastal zone, China - Shuhuan Du; Baosheng Li; Rong Xiang; Dongfeng Niu; Yuejun Si (Arabian Journal of Geosciences, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

Simultaneous determination of three pesticides and their metabolites in unprocessed foods using ultraperformance liquid chromatography-tandem mass spectrometry - Lili Rong; Xiaohu Wu; Jun Xu; Fengshou Dong; Xingang Liu; Xinglu Pan; Pengqiang Du; Dongmei Wei; Yongquan Zheng (Food Additives & Contaminants: Part A, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Inflammation Induced by Candida parapsilosis in THP-1 Cells and Human Peripheral Blood Mononuclear Cells (PBMCs) - Zhimin Duan; Xu Chen; Leilei Du; Caixia Liu; Rong Zeng; Qing Chen; Min Li (Mycopathologia, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Changes in intermediate water conditions in the northern South China Sea using Globorotalia inflata over the last 20 ka - Yiping Yang; Rong Xiang; Jianguo Liu; Shaoying Fu; Liping Zhou; Shuhuan Du; Honghong Lü (Journal of Quaternary Science, 2017)
Intermediate circulation is one of the crucial controls of thermohaline changes in seawater. Due to the lack of data for some of the more significant indicators, there has been little research into past intermediate waters in the South China Sea (SCS). In particular, little is known of the thermohaline properties of intermediate water. Here, we present paired Mg/Ca and δ 18 O data for the planktonic foraminifera Globorotalia inflata from core GHE27L in the northern SCS; these data provide records of temperature and residual δ 18 O seawater (δ 18 O residual , being used as a proxy for salinity) to tentatively investigate changes in the intermediate water of the SCS over the last 20 ka. Our results show that G. inflata in the SCS grew principally within the 200–450 m water depth interval. Thermohaline changes recorded by G. inflata indicate warm and relatively freshening water during the Last Glacial Maximum (LGM, 20–17.7 ka BP ), changing to warm and saline waters between 17.7 and 13.6 ka BP . In general, waters during the 13.6–8.3 ka BP period were characterized by high temperatures and salinity, with obvious millennial‐scale fluctuations, after which, during the Holocene, they became cold and fresh. We suggest that the temperature and salinity of the intermediate water of the SCS recorded by G. inflata in core GHE27L were possibly associated with a switch in intermediate water masses. During the LGM, the intermediate water in the northern SCS was mainly impacted by North Pacific Intermediate Water (NPIW), but that subsequently the influence of Antarctic Intermediate Water strengthened during the last deglaciation and Pre‐Boreal period (17.7–8.3 ka BP ). After this period, NPIW was the principal control of the intermediate water of the SCS again.

Erratum to: Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Philippe Bouvet; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

Enhanced delivery of biodegradable mPEG-PLGA-PLL nanoparticles loading Cy3-labelled PDGF-BB siRNA by UTMD to rat retina - Jing Du; Ying Sun; Feng-Hua Li; Lian-Fang Du; You-Rong Duan (Journal of Biosciences, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

The genome sequence of Brassica campestris chrysovirus 1, a novel putative plant-infecting tripartite chrysovirus - Jun Zhang; Zhonghao Zhao; Rong Hu; Lingfang Guo; Limin Zheng; Zhenguo Du; Zujian Wu; Shouguo Fang; Songbai Zhang; Yong Liu (Archives of Virology, 2017)

Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Slow-release nitrogen fertilizers can improve yield and reduce Cd concentration in pakchoi (Brassica chinensis L.) grown in Cd-contaminated soil - Ran-Ran Zhang; Yue Liu; Wan-Lei Xue; Rong-Xin Chen; Shao-Ting Du; Chong-Wei Jin (Environmental Science and Pollution Research, 2016)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

The influence of potassium concentration on epileptic seizures in a coupled neuronal model in the hippocampus - Mengmeng Du; Jiajia Li; Rong Wang; Ying Wu (Cognitive Neurodynamics, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Activation of Transient Receptor Potential Vanilloid 4 is Involved in Neuronal Injury in Middle Cerebral Artery Occlusion in Mice - Pinghui Jie; Zihong Lu; Zhiwen Hong; Lin Li; Libin Zhou; Yingchun Li; Rong Zhou; Yebo Zhou; Yimei Du; Lei Chen; Ling Chen (Molecular Neurobiology, 2016)

(2R,3S)-Pinobanksin-3-cinnamate improves cognition and reduces oxidative stress in rats with vascular dementia - Hong Liu; Min Zhao; Shen Yang; Dian-Rong Gong; De-Zhe Chen; De-Yong Du (Journal of Natural Medicines, 2015)

Multilocus sequence typing analysis of Cronobacter spp. isolated from China - Jing-Hua Cui; Xiao-Li Du; Rong-Jie Wei; Hai-Jian Zhou; Wei Li; Stephen Forsythe; Zhi-Gang Cui (Archives of Microbiology, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana under various nutrient conditions - Xin-Xin Ai; Jun-Rong Liang; Ya-Hui Gao; Samuel Chun-Lap Lo; Fred Wang-Fat Lee; Chang-Ping Chen; Chun-Shan Luo; Chao Du (Journal of Applied Phycology, 2015)

Effects of Estradiol on Voltage-Gated Potassium Channels in Mouse Dorsal Root Ganglion Neurons - Juan Du; Qiang Wang; Fang Hu; Jun Wang; Haixia Ding; Rong Gao; Hang Xiao; Lin Wang (The Journal of Membrane Biology, 2014)

Depression in older patients with advanced colorectal cancer is closely connected with immunosuppressive acidic protein - Rong Li; Jie Yang; Jihua Yang; Weijun Fu; Hua Jiang; Juan Du; Chunyang Zhang; Hao Xi; Jian Hou (Metabolic Brain Disease, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Expression of a potato antimicrobial peptide SN1 increases resistance to take-all pathogen Gaeumannomyces graminis var. tritici in transgenic wheat - Wei Rong; Lin Qi; Jingfen Wang; Lipu Du; Huijun Xu; Aiyun Wang; Zengyan Zhang (Functional & Integrative Genomics, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Phylogenetic and pathogenic analyses of two virulent Newcastle disease viruses isolated from Crested Ibis (Nipponia nippon) in China - Shengli Chen; Huafang Hao; Qingtian Liu; Rong Wang; Peng Zhang; Xinglong Wang; Enqi Du; Zengqi Yang (Virus Genes, 2013)

Gene cloning and functional analysis of yellow green leaf3 (ygl3) gene during the whole-plant growth stage in rice - Xiaoqing Tian; Yinghua Ling; Likui Fang; Peng Du; Xianchun Sang; Fangming Zhao; Yunfeng Li; Rong Xie; Guanghua He (Genes & Genomics, 2013)

Effects of 24-epibrassinolide on ascorbate–glutathione cycle and polyamine levels in cucumber roots under Ca(NO3)2 stress - Ling-Yun Yuan; Jing Du; Ying-Hui Yuan; Sheng Shu; Jin Sun; Shi-Rong Guo (Acta Physiologiae Plantarum, 2013)

Design and synthesis of novel pyrethriods containing eugenol moiety - Xinlong Wang; Meigui Yi; Quanhai Du; Aimin Wu; Rong Xiao (Medicinal Chemistry Research, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Effect of insulin on dexamethasone-induced ultrastructural changes in skeletal and cardiac muscle - Jian Qin; Rong Du; Yaqun Yang; Hongqiang Zhang; Ying Zhou (Biologia, 2012)

A precise velocity field of tectonic deformation in China as inferred from intensive GPS observations - Qiang Li; XinZhao You; ShaoMin Yang; RuiLin Du; XueJun Qiao; Rong Zou; Qi Wang (Science China Earth Sciences, 2012)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Cordyceps cicadae extracts ameliorate renal malfunction in a remnant kidney model - Rong Zhu; Yi-ping Chen; Yue-yi Deng; Rong Zheng; Yi-fei Zhong; Lin Wang; Lan-ping Du (Journal of Zhejiang University-SCIENCE B, 2011)

Validation and dissection of quantitative trait loci for leaf traits in interval RM4923-RM402 on the short arm of rice chromosome 6 - BO SHEN; WEI-DONG YU; JING-HONG DU; YE-YANG FAN; JI-RONG WU; JIE-YUN ZHUANG (Journal of Genetics, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Parasitism and olfactory responses of Dastarcus helophoroides (Coleoptera: Bothrideridae) to different Cerambycid hosts - Jian-Rong Wei; Zhong-Qi Yang; Therese M. Poland; Jia-Wei Du (BioControl, 2009)

Comparison of four molecular markers for genetic analysis in Diospyros L. (Ebenaceae) - X. Y. Du; Q. L. Zhang; Zheng-Rong Luo (Plant Systematics and Evolution, 2009)

Effects of a Copper-Resistant Fungus on Copper Adsorption and Chemical Forms in Soils - Aixue Du; Lixiang Cao; Renduo Zhang; Rong Pan (Water, Air, & Soil Pollution, 2009)

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Active extracts of wild fruiting bodies of Antrodia camphorata (EEAC) induce leukemia HL 60 cells apoptosis partially through histone hypoacetylation and synergistically promote anticancer effect of trichostatin A - Mei-Chin Lu; Ying-Chi Du; Jiunn-Jye Chuu; Shiuh-Lin Hwang; Pao-Chuan Hsieh; Chih-Sheng Hung; Fang-Rong Chang; Yang-Chang Wu (Archives of Toxicology, 2009)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Protection against hydrogen peroxide-induced injury by Z-ligustilide in PC12 cells - Yan Yu; Jun-Rong Du; Chen-Yuan Wang; Zhong-Ming Qian (Experimental Brain Research, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Benzo[a]pyrene-induced cell cycle progression is through ERKs/cyclin D1 pathway and requires the activation of JNKs and p38 mapk in human diploid lung fibroblasts - Hong Ju Du; Ning Tang; Bing Ci Liu; Bao Rong You; Fu Hai Shen; Meng Ye; Ai Gao; Chuan Shu Huang (Molecular and Cellular Biochemistry, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)